Chemical chromatin ubiquitylation. (August 2018) - Jbara, Muhammad; Sun, Hao; Kamnesky, Guy; Brik, Ashraf
Graphical abstract: Abstract : Histone modifications dynamically regulate chromatin structure and function, thereby mediating many processes that require access to DNA. Chemical protein synthesis has emerged as a powerful approach for generating homogeneously modified histone analogues in workable amounts for subsequent incorporation into nucleosome arrays for biochemical, functional and structural studies. This short review focuses on the strength of total chemical protein synthesis and semisynthetic approaches to generate ubiquitylated histones in their native or non-native forms and the utility of these analogues to decode the role of ubiquitylation in epigenetics.